Efficacy and safety of anti-CD19 CAR T-cell therapy in 110 patients with B-cell acute lymphoblastic leukemia with high-risk features - Zhang, Xian (Blood Adv, 2020)
Anti-CD19 chimeric antigen receptor (CAR) T-cell therapy is effective in patients with advanced B-cell acute lymphoblastic leukemia (B-ALL). However, efficacy data is sparse in subgroups of patients with high-risk features such as BCR-ABL(+), TP53 mutation, extramedullary disease (including central nervous system leukemia) or posttransplant relapse. It is also uncertain whether there is an added benefit of transplantation after anti-CD19 CAR T-cell therapy. We conducted a phase 1/2 study of 115 enrolled patients with CD19(+) B-ALL. A total of 110 patients were successfully infused with anti-CD19 CAR T cells. In all, 93% of patients achieved a morphologic complete remission, and 87% became negative for minimal residual disease. Efficacy was seen across all subgroups. One-year leukemia-free survival (LFS) was 58%, and 1-year overall survival (OS) was 64% for the 110 patients. Seventy-five nonrandomly selected patients (73.5%) subsequently received an allogeneic hematopoietic stem cell transplant (allo-HSCT). LFS (76.9% vs 11.6%; P < .0001; 95% confidence interval [CI], 11.6-108.4) and OS (79.1% vs 32.0%; P < .0001; 95% CI, 0.02-0.22) were significantly better among patients who subsequently received allo-HSCT compared with those receiving CAR T-cell therapy alone. This was confirmed in multivariable analyses (hazard ratio, 16.546; 95% CI, 5.499-49.786). Another variate that correlated with worse outcomes was TP53 mutation (hazard ratio, 0.235; 95% CI, 0.089-0.619). There were no differences in complete remission rate, OS, or LFS between groups of patients age 2 to 14 years or age older than 14 years. Most patients had only mild cytokine release syndrome and neurotoxicity. Our data indicate that anti-CD19 CAR T-cell therapy is safe and effective in all B-ALL subgroups that have high-risk features. The benefit of a subsequent allo-HSCT requires confirmation because of nonrandom allocation. This trial was registered at www.clinicaltrials.gov as #NCT03173417.